Method for manufacturing diamond particles

CN118414303BActive Publication Date: 2026-10-27唐捷
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202280084582.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-12-21
Filing Date
2022-12-21
Publication Date
2026-10-27
Estimated Expiration
2042-12-21

AI Technical Summary

Technical Problem

作为合成金刚石颗粒的方法,已知高压合成法、化学气相生长法和爆炸法等,但是任意一种方法均使用大型的装置在密闭空间内进行,因此生产率存在问题

Benefits of technology

[0019]根据本发明,仅通过将含有碳原子的有机溶剂与无机盐混合、进行熟化,就可以合成金刚石颗粒,因此无需特殊的技术、昂贵的设备,生产率优异。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118414303B_ABST
    Figure CN118414303B_ABST
Patent Text Reader

Abstract

Provided is a method for producing diamond particles that can be synthesized in a solution using a simpler method. The method includes a process (S1) of preparing a mixed solution by mixing an inorganic salt such as a metal halide, a metal oxyhalide, a metal nitrate, a metal phosphate, and a metal sulfate in a solvent containing 10% by volume or more of an organic solvent such as an alcohol-based solvent, a ketone-based solvent, an ester-based solvent, an amide-based solvent, a hydrocarbon-based solvent, an aromatic-based solvent, a cellosolve-based solvent, and a halogen-based solvent, and a ripening process (S2) of keeping the mixed solution at an arbitrary temperature for a certain period of time, thereby generating diamond particles in a solution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for manufacturing diamond particles, and more specifically to a technique for liquid-phase synthesis of diamond particles. Background Technology

[0002] Diamond is known to possess not only high hardness but also high thermal conductivity, high resistivity, excellent chemical resistance, low coefficient of thermal expansion, low coefficient of friction, wide light transmission wavelength band, and the ability to be synthesized bio-based, among other unique properties, making its wide application in the electronics field highly anticipated. Methods for synthesizing diamond particles include high-pressure synthesis, chemical vapor deposition, and explosive methods; however, all of these methods require large-scale equipment in a confined space, thus presenting challenges in productivity.

[0003] In addition, previously, as a method for synthesizing fine particles in solution, a solvothermal method for synthesizing nanoparticles has been proposed (see, for example, Patent Document 1). The method described in Patent Document 1 involves coexisting a liquid mixture containing a nanoparticle precursor and a surfactant with an organic solvent, and forming nano-sized particles in the presence of the organic solvent in a reaction field that is in a supercritical or subcritical state. Diamond is described as an example of fine particles that can be synthesized.

[0004] Existing technical documents

[0005] Patent documents

[0006] Patent Document 1: Japanese Patent Application Publication No. 2009-233845 Summary of the Invention

[0007] The problem the invention aims to solve

[0008] However, Patent Document 1, mentioned above, does not disclose any specific method for synthesizing diamond nanoparticles. Furthermore, the method described in Patent Document 1 requires supercritical or subcritical reactions within an autoclave, thus still presenting challenges in improving productivity. Therefore, there is a need to develop a liquid-phase synthesis method for diamond particles that requires no special technology or expensive equipment and offers excellent productivity.

[0009] Therefore, the object of the present invention is to provide a method for manufacturing diamond particles that can be synthesized in solution using a simpler method.

[0010] Solution for solving the problem

[0011] The inventors of this application discovered that diamond particles can be synthesized simply by aging a mixed solution that will become a raw material, thus completing this invention.

[0012] That is, the method for manufacturing diamond particles of the present invention includes: a step of preparing a mixed solution by mixing an inorganic salt in a solvent containing 10% by volume or more of an organic solvent containing carbon atoms; and a aging step of maintaining the aforementioned mixed solution at any temperature for a certain period of time.

[0013] As the aforementioned organic solvent, at least one selected from the group consisting of alcohol solvents, ketone solvents, ester solvents, amide solvents, hydrocarbon solvents, aromatic solvents, cellosol solvents, and halogen solvents can be used. Among these organic solvents, organic solvents containing alkyl groups having sp3 hybrid orbitals are particularly preferred.

[0014] As the aforementioned inorganic salt, for example, at least one selected from the group consisting of metal halides, metal oxyhalides, metal nitrates, metal phosphates, and metal sulfates can be used. In this case, the aforementioned inorganic salt may contain metal ions of Group 1 elements, Group 2 elements, Group 13 elements, or transition metal elements.

[0015] The concentration of the aforementioned inorganic salt in the aforementioned mixed solution can be set, for example, from 0.001 to 1000 g / L.

[0016] In the aforementioned curing process, the aforementioned mixed solution can be maintained at a temperature of 0 to 400°C for 0.1 to 1000 hours. Alternatively, the aforementioned mixed solution can be maintained at atmospheric pressure or at the saturated vapor pressure of the aforementioned organic solvent.

[0017] When using the diamond particle manufacturing method of the present invention, diamond particles with a crystal structure having cubic and / or hexagonal crystals and a particle size of 1 to 100 nm can be obtained, for example.

[0018] The effects of the invention

[0019] According to the present invention, diamond particles can be synthesized simply by mixing an organic solvent containing carbon atoms with an inorganic salt and aging it, thus requiring no special technology or expensive equipment and achieving excellent productivity. Attached Figure Description

[0020] Figure 1 A flowchart illustrating a method for manufacturing diamond particles according to an embodiment of the present invention.

[0021] Figure 2 The figure is used to schematically illustrate a method for manufacturing diamond particles according to an embodiment of the present invention.

[0022] Figure 3 TEM image of diamond particles synthesized using Example 1 (attached photograph).

[0023] Figure 4TEM image of diamond particles synthesized using Example 2 (photograph for illustrative purposes only).

[0024] Figure 5 Images A through D are HR-TEM images (substitute photographs) obtained by observing diamond particles synthesized using Example 1 from various crystal orientations.

[0025] Figure 6 A through D are HR-TEM images (substitute photographs) obtained by observing diamond particles synthesized using Example 2 from various crystal orientations.

[0026] Figure 7 Images A and B are HR-TEM images of other diamond particles synthesized using Example 2 (substitute photographs in the accompanying drawings).

[0027] Figure 8 HR-TEM images of other diamond particles synthesized using Example 2 (see attached photographs). Detailed Implementation

[0028] The following detailed description of methods for implementing the present invention is provided with reference to the accompanying drawings. It should be noted that the present invention is not limited to the embodiments described below.

[0029] Figure 1 This is a flowchart illustrating the method for manufacturing diamond particles according to this embodiment. Figure 2 This is for illustrative purposes only. (For example...) Figure 1 and Figure 2 As shown, the method for manufacturing diamond particles according to an embodiment of the present invention is carried out in the following steps: step S1 of preparing a mixed solution; and step S2 of aging the mixed solution.

[0030] [Step S1: Mixed Solution Preparation Process]

[0031] In the mixed solution preparation step S1, a solvent containing an organic solvent with carbon elements and an inorganic salt are mixed to prepare a mixed solution.

[0032] <Solvent>

[0033] The organic solvent contained in the solvent may contain carbon atoms, preferably alcohol solvents, ketone solvents, ester solvents, amide solvents, hydrocarbon solvents, aromatic solvents, cellosol solvents and halogen solvents, which may be used alone or in combination.

[0034] From the viewpoint of ease of acquisition, alcohol solvents are preferably methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, isobutanol, tert-butanol, 1-pentanol, and allyl alcohol.

[0035] From the viewpoint of ease of acquisition, ketone solvents are preferably acetone, acetylacetone, methyl ethyl ketone, isopropyl methyl ketone, isobutyl methyl ketone, 2-pentanone, 3-pentanone, cyclohexanone, and diketone.

[0036] From the viewpoint of ease of acquisition, ester solvents are preferably ethyl acetate, propylene glycol monomethyl ether acetate, and 2-ethoxyethyl acetate.

[0037] From a general viewpoint, amide solvents are preferably N-methylpyrrolidone (NMP), N-ethyl-2-pyrrolidone, N-cyclohexyl-2-pyrrolidone, N,N-dimethylformamide (DMF), and N,N-dimethylacetamide.

[0038] The hydrocarbon solvent preferably has a methyl group (-CH3), and more specifically, it is preferably n-hexane, n-heptane, n-octane, n-decane, n-dodecane, 2,3-dimethylhexane, 2-methylheptane, 2-methylhexane, 3-methylhexane and cyclohexane.

[0039] From the viewpoint of ease of acquisition, aromatic solvents are preferably benzene, toluene, xylene, trimethylbenzene, ethylbenzene, methylnaphthalene, ethylnaphthalene, and dimethylnaphthalene.

[0040] From the viewpoint of ease of acquisition, the solvents for the cellosol system are preferably methyl cellosol, ethyl cellosol, butyl cellosol, diethylene glycol monomethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, and triethylene glycol monomethyl ether.

[0041] From the viewpoint of ease of acquisition, halogen solvents are preferably dichloromethane, trichloromethane, carbon tetrachloride, and chloroform.

[0042] Among the aforementioned organic solvents, those containing alkyl groups with sp3 hybrid orbitals, such as methyl (-CH3), are particularly preferred. Organic solvents containing alkyl groups with sp3 hybrid orbitals facilitate the replacement of hydrogen (H) atoms with carbon (C) atoms through inorganic salts, forming the diamond core and thus promoting the formation of diamond particles.

[0043] The solvent mixed in the solution may consist solely of an organic solvent containing carbon atoms, or it may contain water in addition to an organic solvent. If the solvent contains water, the inorganic salt is readily soluble. When the solvent contains water, the volume of the organic solvent relative to the total volume is preferably 10% by volume or more and less than 100% by volume, more preferably 50% to 90% by volume.

[0044] <Inorganic Salts>

[0045] The inorganic salt functions as a catalyst in the curing step S2 described later, whereby diamond particles are formed from the solvent. The inorganic salt mixed in the mixed solution is preferably at least one selected from metal halides, metal oxyhalides, metal nitrates, metal phosphates, and metal sulfates. Among these inorganic salts, halides are particularly preferred because they can readily abstract other atoms bonded to carbon atoms in the organic solvent.

[0046] The inorganic salt mixed in the mixed solution preferably contains metal ions of Group 1, Group 2, Group 13, or transition metal elements. Examples of Group 1 elements in the inorganic salt include lithium (Li), sodium (Na), and potassium (K). Examples of Group 2 elements include beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), and barium (Ba).

[0047] As Group 13 elements, examples include aluminum (Al), gallium (Ga), and indium (In). The transition metals also include lanthanides, such as scandium (Sc), titanium (Ti), chromium (Cr), cobalt (Co), nickel (Ni), copper (Cu), molybdenum (Mo), niobium (Nb), lanthanum (La), cerium (Ce), and neodymium (Nd).

[0048] The concentration of inorganic salt in the mixed solution is not particularly limited, but diamond particles are formed if it is in the range of 0.001 to 1000 g / L. The concentration of inorganic salt in the mixed solution is preferably 0.1 to 10 g / L, which improves the yield. It should be noted that, from the viewpoint of improving yield, the concentration of inorganic salt in the mixed solution is more preferably 0.3 to 5 g / L, and even more preferably 0.5 to 1.5 g / L.

[0049] When mixing a solvent containing an organic solvent with carbon and an inorganic salt, it is preferable to use an ultrasonic homogenizer or a high-pressure homogenizer for ultrasonic dispersion.

[0050] [Step S2: Curing Process]

[0051] In the curing step S2, the mixed solution prepared in the mixed solution preparation step S1 is kept at any temperature for a certain period of time. For curing the mixed solution, keeping it for a certain time is sufficient; preferably, it is kept at a temperature of 0–400°C for 0.1–1000 hours, more preferably at a temperature of 10–250°C for 20–200 hours. By curing under these conditions, diamond particles can be generated in the mixed solution.

[0052] The aging of the mixed solution can be carried out at atmospheric pressure or at the saturated vapor pressure of the solvent constituting the mixed solution. If aging is carried out at the saturated vapor pressure of the solvent, the formation of diamond particles is promoted, and thus the holding time can be shortened to the range of 10 to 30 hours.

[0053] [Other processes]

[0054] Following the aforementioned aging process S2, a process can be performed to remove the solvent from the mixed solution, recover the product, and perform washing. This removes the inorganic salts, yielding diamond particles.

[0055] [Diamond particles]

[0056] When using the diamond particle manufacturing method of this embodiment described above, diamond particles with a cubic and / or hexagonal crystal structure and a particle size of 0.5 nm or more and 1 mm or less can be obtained. Due to their clean surface and impurity-free characteristics, these diamond particles are suitable for applications such as fluorescent semiconductor quantum dots, nanoscale magnetic sensors, in vivo tracking, and drug delivery.

[0057] Cubic diamond particles belong to the Fd3 ̄m space group (International Tables for Crystallography No. 227). Hexagonal diamond particles belong to the P63 / mmc space group (International Tables for Crystallography No. 194). The crystal structure of diamond particles can be easily determined by measuring electron diffraction or high-speed Fourier transform (FFT) patterns.

[0058] The diamond particles manufactured using the method of this embodiment are preferably single-crystal particles with a particle size of 1 to 100 nm. If they fall within this range, they can be applied to the aforementioned uses. It should be noted that the particle size of the diamond particles is more preferably 1 to 60 nm. The particle size of the diamond particles referred to herein is the value obtained by averaging the particle size of 100 randomly selected particles from images observed using a transmission electron microscope (TEM).

[0059] Diamond particles manufactured using the method of this embodiment can have defects within a single particle. These defects can be twins and / or stacking faults. Even with defects, diamond particles manufactured using the method of this embodiment can maintain a clean surface and impurity-free properties.

[0060] The inventors are not yet aware of the mechanism by which diamond particles are generated using a liquid-phase synthesis method involving an organic solvent containing carbon atoms and an inorganic salt, but believe it to be as follows: When the carbon atoms in the organic solvent have sp3 hybrid orbitals or readily form sp3 hybrid orbitals, it is believed that the inorganic salt, acting as a catalyst, abstracts atoms other than the carbon atoms bonded to the carbon atoms, forming C-C bonds. For example, when the organic solvent has a CH3 group and a chloride is used as the salt, it is believed that the tetrahedral configuration of the CH3 group... - H is replaced by Cl to become CCl4, and Cl is replaced by C to become a diamond structure with C-C bonds.

[0061] As detailed above, the diamond manufacturing method of this embodiment synthesizes diamond particles in solution by aging a mixture of an organic solvent containing carbon atoms and an inorganic salt. Therefore, it requires no special technology or expensive equipment and boasts excellent productivity. The diamond particles obtained in this way have a clean surface and are free of impurities, making them suitable for fluorescent semiconductor quantum dots, nanoscale magnetic sensors, and, when used for in vivo tracking, for monitoring the implantation and regeneration capabilities of stem cells.

[0062] Example

[0063] The effects of the present invention will be specifically described below using embodiments of the present invention. In this embodiment, diamond particles are synthesized under the conditions shown in Table 1 below. Specifically, inorganic salts shown in Table 1 are added to a solvent consisting only of organic solvents (50 mL) at a specified concentration to obtain a mixed solution, which is then aged under the conditions shown in Table 1.

[0064] [Table 1]

[0065]

[0066] The products obtained in each example were washed multiple times with ethanol and then evaluated using a transmission electron microscope (TEM, JEM-2100F, NEC Corporation). The results are as follows: Figures 3-8 And as shown in Table 2 below.

[0067] [Table 2]

[0068]

[0069] Figure 3 This is a TEM image of the diamond particles synthesized in Example 1. Figure 4 This is a TEM image of the diamond particles synthesized in Example 2. Figure 3 and Figure 4 As shown, in Examples 1 and 2, black particles are generated to demonstrate contrast. Figure 3 Particles with diameters ranging from 1 to 60 nm were observed. Figure 4 Particles with diameters ranging from 1 to 30 nm were observed. The average particle size was determined using ImageJ (ver. 1.51n; an open-source and public domain image processing software). The results showed that the average particle size of the particles in Example 1 was 8 nm, and the average particle size of the particles in Example 2 was 12 nm. In addition, the particles synthesized in Examples 3 to 10 also exhibited the same characteristics.

[0070] Figure 4 The selected area electron diffraction (SAED) pattern of the particles from Example 2 is shown, exhibiting clear Bragg reflection. Miller indices were used for index calibration, and in addition to the reflections at {111}, {220}, {311}, {400}, and {331} due to the cubic diamond structure, reflection at {200} was also confirmed. This indicates that the obtained particles are diamond particles with a cubic crystal structure. It should be noted that the reflection at {200} is presumably due to the extinction reflection of the cubic diamond structure belonging to the Fd3 ̄m space group, resulting from multiple scattering effects. Furthermore, the particles from Examples 1, 3-10 were also similarly confirmed to be diamond particles with a cubic crystal structure.

[0071] Figure 5 Images A through D are HR-TEM images obtained from observation of the diamond particles synthesized in Example 1 from various crystal orientations. Figure 6 Images A through D are HR-TEM images obtained by observing the diamond particles synthesized in Example 2 from various crystal orientations. Figure 5 and Figure 6 Images A through D are HR-TEM images and FFT diffraction patterns of diamond particles along

[100] ,

[110] ,

[111] , and

[112] , respectively. Figure 5 and Figure 6 It was confirmed that the diamond particles synthesized in Examples 1 and 2 were single crystals. Furthermore, the diamond particles in Examples 3 to 10 were also single crystals.

[0072] Figure 7 A and B are HR-TEM images of other diamond particles synthesized in Example 2, which are HR-TEM images and FFT diffraction patterns of diamond particles along

[100] and

[001] , respectively. Figure 7 Hexagonal diamond particles were found in samples A and B, confirming them to be single-crystal particles with a hexagonal crystal structure. Furthermore, samples 1, 3-10 also confirmed that some diamond particles similarly possessed a hexagonal crystal structure.

[0073] Figure 8The images show HR-TEM images of other diamond particles synthesized in Example 2. Figure 8 Diamond particles exhibiting twinning and stacking faults were observed. Furthermore, particles with crystallographic defects were also observed in the diamond particles of Examples 1, 3-10.

[0074] The above results confirm that, according to the present invention, diamond particles can be synthesized in solution using a simpler method.

Claims

1. A method for manufacturing diamond particles, comprising: The process of preparing a mixed solution by mixing an inorganic salt in a solvent containing at least 10% by volume of an organic solvent containing carbon atoms; and The mixture is aged at a temperature of 0-400°C for 0.1-1000 hours. The inorganic salt is a metal halide. The solvent is composed of an organic solvent containing carbon atoms and water, and the organic solvent accounts for more than 10% by volume relative to the total solvent volume, or it is composed solely of an organic solvent containing carbon atoms. The organic solvent containing carbon atoms is at least one selected from the group consisting of alcohol solvents, ketone solvents, ester solvents, amide solvents, hydrocarbon solvents, aromatic solvents, cellosol solvents, and halogen solvents. The mixed solution consists of the solvent and the inorganic salt.

2. The method for manufacturing diamond particles according to claim 1, wherein, The organic solvent contains alkyl groups having sp3 hybrid orbitals.

3. The method for manufacturing diamond particles according to claim 1, wherein, The inorganic salt contains metal ions of Group 1, Group 2, Group 13 elements or transition metal elements.

4. The method for manufacturing diamond particles according to claim 1, wherein, The concentration of the inorganic salt in the mixed solution is 0.001~1000 g / L.

5. The method for manufacturing diamond particles according to claim 1, wherein, The aging process involves maintaining the mixed solution at the saturated vapor pressure of the solvent.

6. The method for manufacturing diamond particles according to any one of claims 1 to 5, wherein, Diamond particles with a crystal structure of cubic and / or hexagonal crystals and a particle size of 1~100nm were obtained.

Citation Information

Patent Citations

  • Method for synthesizing nanoparticle using solvothermal method

    JP2009233845A

  • Method for producing diamond

    JP2021178747A